Cognitive impairment in different hemodialysis techniques - Mahmoud Mohamed Abdelsalam Abdelwahab; Youmna Sabri; Ibrahim Hamdey Rashed Elkalla; Mohammed Kamal Nassar; Sara M. Abdel-Gawad; Zinab Abo Elfotouh Gomaa (Middle East Current Psychiatry, 2022)
Abstract Background Cognitive impairment is one of the most common, often untreated, comorbidities affecting patients with chronic kidney disease treated with hemodialysis. Increased mortality, poor compliance, depression, and poor quality of life were all linked to cognitive impairment in the hemodialysis population. The intradialytic exercise proved to be beneficial in improving patients’ quality of life, among other positive effects. Cooling dialysate has various positive effects, including improved patients’ mood and decreased hypotensive episodes during hemodialysis. The study aims to assess the effect of intradialytic exercise and cool hemodialysis on cognitive function in patients on hemodialysis. Results The study showed no significant effect of both interventions on the patient’s cognitive functions. However, cooling dialysate showed an improvement in the severity of depressive symptoms by Beck’s Depression Inventory II (p = 0.02). On the other hand, Mini-International Neuropsychiatric Interview showed an increase of patients diagnosed with depression in the intradialytic exercise group. Conclusions Both interventions had no significant effect on the mean scores of the Montreal Cognitive Assessment, which are lower in our sample than in the general population (23.9–25). Potential implications include the importance of managing psychiatric comorbidities in patients on hemodialysis. Cooling dialysate can be adopted to alleviate depressive symptoms in patients on hemodialysis.